Clinical insights into heterogeneity of rheumatoid factor negative polyarticular juvenile idiopathic arthritis across the world - Naddei, Roberta; Burrone, Marco; Ridella, Francesca; Uziel, Yosef; Trachana, Maria; Dolezalova, Pavla; Rumba-Rozenfelde, Ingrida; Ruperto, Nicolino; Ravelli, Angelo; Consolaro, Alessandro (Pediatric rheumatology online journal, 2025)
BACKGROUND: To our knowledge, limited information is available about the differences in the characteristics of rheumatoid factor (RF)-negative polyarticular juvenile idiopathic arthritis (JIA) throughout the world. This study was aimed to compare the demographic and clinical features of patients with RF-negative polyarthritis across the world. METHODS: Patients were part of a multinational sample included in a study aimed to investigate the prevalence of disease categories, treatment regimens, and disease status in patients from different geographical areas (EPOCA Study). All patients underwent a retrospective assessment, based on the review of clinical chart, and a cross-sectional evaluation, which included assessment of physician- and parent-reported outcomes and collection of ongoing medications. RESULTS: Among the 9081 patients enrolled in the EPOCA study, 2141 patients (23.6%) with RF-negative polyarthritis were included in the present analysis. The prevalence of RF-negative polyarthritis was highest in North America and lowest in Southeast Asia (12.7%). The age at disease onset was lower in Northern and Southern Europe, where the highest prevalence of uveitis was found. Uveitis was rare in Southeast Asia, Africa & Middle East and Latin America. Patients from Eastern Europe, Latin America and Africa and Middle East presented with the highest prevalence of active joints at the visit. The combination of early onset, ANA positivity, and uveitis was observed mainly in Southern Europe (39%). CONCLUSIONS: Our results confirm the wide heterogeneity of the clinical presentation and outcome of children with RF-negative polyarticular JIA throughout the world. In particular, relevant differences in the onset age were observed across geographic areas. The group of children with early onset polyarthritis, ANA positivity, and risk of uveitis is remarkably frequent in Southern Europe.
Keywords: věk při počátku nemoci; Age of Onset; juvenilní artritida; lidé; mladiství; celosvětové zdraví; Arthritis, Juvenile; Female; Rheumatoid Factor; dítě; Evropa; Prevalence; retrospektivní studie; Uveitis; Adolescent; Humans; průřezové studie; Cross-Sectional Studies; předškolní dítě; Child, Preschool; uveitida; mužské pohlaví; antirevmatika; ženské pohlaví; prevalence; Male; revmatoidní faktor; Europe; Retrospective Studies; Antirheumatic Agents; Child; Global Health